Persepsi Terhadap Organisasi Ditinjau Dari Minat Berorganisasi Mahasiswa Jurusan Keperawatan Universitas Ratu Samban - Zuraida Zuraida (Jurnal Ilmiah Psyche, 2023)
Nursing students at Ratu Samban University have low interest in joining organizations on campus. It is assumed that students have a negative perception of the organization. This study aims to examine the relationship between perceptions of organization and organizational interest in students majoring in nursing at Ratu Samban University. The variables of perception and interest in organizing are measured using a scale. The subjects of this study were 50 students majoring in nursing at Ratu Samban University. The sampling technique in this study used a probability sampling technique. The analysis technique used in this research is quantitative analysis using the product moment of Karl Pearson with the SPSS Version 20 for Windows program. Based on the results of the study, it is known that perceptions of organization have a positive relationship with organizational interest in students majoring in nursing at Ratu Samban University. There is a significant correlation (r.0.865 with significance <0.05) between the variable perceptions of organization and interest in organizing among students majoring in nursing, namely 0.000 and the significance value is below/smaller than 0.05, this means that there is a relationship between perceptions of organization and interest in organizing to students majoring in nursing at Ratu Samban University. The more positive the perception of the organization, the higher the interest in organizing and conversely the more negative the perception of the organization, the lower the student's interest in organizing. For students majoring in nursing, perceptions of organization have the most negative perceptions with a contribution of 46% and interest in organizing has the most low-level categories with a contribution of 56%.